Significance of 18S rDNA specific primers in the identification of genus Dunaliella - P. Ramesh Kannan, S. Divya; R. Rengasamy, K.R. Jayappriyan*, R. Rajkumar (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The cells survive in extreme marine environments has received significant interest due to their high valuable compounds. In the present attempt, a total of six different isolates of Dunaliella isolated from the salt pans of Andhra Pradesh, India were identified based on their morphology and cultural characteristics. Besides, the isolates were subjected to molecular identification using 18S rDNA specific primers. Out of the six isolate one was never amplified with the any of species specific primers used hence it was partially sequenced and submitted in GenBank. This study obviously describes the incidence of non carotenogenic strains (never turn from green to red) of Dunaliella bardawil and Dunaliella parva in natural environment.